Ex vivo enrichment of PRAME antigen‐specific T cells for adoptive immunotherapy using CD137 activation marker selection. Issue 10 (21st October 2020) - Lee, Koon H; Gowrishankar, Kavitha; Street, Janine; McGuire, Helen M; Luciani, Fabio; Hughes, Brendan; Singh, Mandeep; Clancy, Leighton E; Gottlieb, David J; Micklethwaite, Kenneth P; Blyth, Emily
Abstract: Objective: Adoptive immunotherapy with ex vivo expanded tumor‐specific T cells has potential as anticancer therapy. Preferentially expressed antigen in melanoma (PRAME) is an attractive target overexpressed in several cancers including melanoma and acute myeloid leukaemia (AML), with low expression in normal tissue outside the gonads. We developed a GMP‐compliant manufacturing method for PRAME‐specific T cells from healthy donors for adoptive immunotherapy. Methods: Mononuclear cells were pulsed with PRAME 15‐mer overlapping peptide mix. After 16 h, activated cells expressing CD137 were isolated with immunomagnetic beads and cocultured with irradiated CD137 neg fraction in medium supplemented with interleukin (IL)‐2, IL‐7 and IL‐15. Cultured T cells were restimulated with antigen‐pulsed autologous cells after 10 days. Cellular phenotype and cytokine response following antigen re‐exposure were assessed with flow cytometry, enzyme‐linked immunospot (ELISPOT) and supernatant cytokine detection. Detailed phenotypic and functional analysis with mass cytometry and T‐cell receptor (TCR) beta clonality studies were performed on selected cultures. Results: PRAME‐stimulated cultures ( n = 10) had mean expansion of 2500‐fold at day 18. Mean CD3 + percentage was 96% with CD4:CD8 ratio of 4:1. Re‐exposure to PRAME peptide mixture showed enrichment of CD4 cells expressing interferon (IFN)‐γ (mean: 12.2%) and TNF‐α (mean: 19.7%). Central and effector memory cells were 23% and 72%, respectively, with 24% T cells expressing PD1. Mass cytometry showed predominance of Th1 phenotype (CXCR3 + /CCR4 neg /CCR6 neg /Tbet +, mean: 73%) and cytokine production including IL‐2, IL‐4, IL‐8, IL‐13 and GM‐CSF (2%, 6%, 8%, 4% and 11%, respectively). Conclusion: PRAME‐specific T cells for adoptive immunotherapy were enriched from healthy donor mononuclear cells. The products were oligoclonal, exhibited Th1 phenotype and produced multiple cytokines. Abstract : Adoptive immunotherapy with ex vivo expanded tumor‐specific T cells has potential as anticancer therapy. Preferentially expressed antigen in melanoma (PRAME) is an attractive target overexpressed in several cancers including melanoma and acute myeloid leukaemia (AML), with low expression in normal tissue outside the gonads. We developed a GMP‐compliant manufacturing method for PRAME‐specific T cells from healthy donors for adoptive immunotherapy.